First fossil crabs (Crustacea, Decapoda, Brachyura) from the Kerguelen Islands (Miocene) with exceptionally preserved gills. (26th February 2018) - Robin, Ninon; Van Bakel, Barry W.M.; Blanc-Valleron, Marie-Madeleine; Noël, Pierre Y.; Lemaire, Laurent; Charbonnier, Sylvain
Abstract: Kerguelen Islands are predominantly volcanic lands, thus fossil references are very uncommon. However, its Miocene fossils are of specific interest for understanding migration routes of some taxa during the Cenozoic, given the intermediary position of Kerguelen with various continents. Despite this fossil rarity, we studied herein hundreds of nodules corresponding to the sole known fossil brachyurans (and unique Decapoda) from Kerguelen both for their systematics and their preservation. Indeed, these crabs display some internal fragile structures that are rarely fossilized, such as the gills' branchial lamellae, preserved in volume. The preservation of these gills and their diagenetic features were documented through traditional imagery (SEM), including morphological comparison to modern gills, and with petrographic and geochemical analyses (EDS, X-ray diffractometry). Some cheilostome bryozoans were observed as probable foulers of the crabs carcasses. The fossil material corresponds to a new cancrid crab ( Romaleon franciscae n. sp.) and its occurrence may imply a novel route from South America westward for the geographic migration of the genus Romaleon, since its Cretaceous emergence. The cup-shape and the number and the organization of the gills in these fossil Cancridae specimens are similar to those observed in their extant representatives. Gill preservation in 3D is linked to very early phosphatization of the system during diagenesis, as shown by the nodule matrix, and likely to deposition of a thin clayey cover on the soft-tissues. The implication of intrinsic phosphorous in the differential phosphatization of the crabs' anatomy remains difficult to determine.